SPECIATION OF HEAVY METALS AND MICROBIAL CONTAMINANTS IN HARMATTAN DUST WITHIN THE FEDERAL POLYTECHNIC KAURA NAMODA MAIN CAMPUS, ZAMFARA STATE (FUDMA JOURNAL OF SCIENCES, 2024)
Harmattan dust is a natural phenomenon contributing to air pollution due to the presence of heavy metals and microorganisms. This research aimed to determine the speciation of heavy metal and microbial contaminants in Harmattan dust samples within the polytechnic Kaura Namoda. The composite sample of each month, namely, December 2023, January 2024, and February 2024, was collected with the aid of a sterilized petri dish. Five extraction phases were carried out, in order of mobility of the metals: exchangeable ion > metal bound with carbonate > metal bound to iron and manganese oxide > metals bound to organic matter and sulfide > residual phase. This was achieved using Tessie’s method and AAS for extraction and analysis. The result for the heavy metals shows Cr (13.6%) and Zn (25.5%) are more abundant in the exchangeable phases in December and January. Metals bound to Fe and MnO extraction phases have Zn (25.50%) abundance in December and January. The residual phase of extraction shows the highest percentage of pb (95.3%) and nickel (85.40%) for December and January. The bacteria and fungi identified are Bacillus cereus, Staphylococcus, Aspergillum, and Clodosporium, respectively. There is no significant difference in physicochemical parameters between the Harmattan dust samples collected in December, January, and February. The percentages of heavy metals in the Harmattan dust are high in the immobility phase of extraction, and bacterial and fungal levels are high in December and January. There is a need for preventive and protective measures to mitigate the health effects associated with...
Keywords: Speciation; Harmattan Dust; Heavy Metals; Microorganism; Kaura-Namoda